Clinical - epidemiological characteristics of patients deceased by COVID-19 in a national hospital in Lima, Peru: Características clínicoepidemiológicas de pacientes fallecidos por COVID-19 en un hospital nacional de Lima, Perú - Escobar, Gerson (2020)
Introduction: The COVID-19 pandemic has caused more than 70 thousand deaths worldwide. Objective: To describe the characteristics of COVID-19 patients who died in a tertiary hospital. Methods: A descriptive study was carried out in the emergency service of the Hospital Rebagliati in Lima, Peru, which includes deceased patients with a positive result for SARS-CoV-2 infection diagnosed by PCR-TR until April 4, 2020. The medical history was reviewed. and hospital records looking for sociodemographic variables, clinical characteristics, radiological manifestations, treatment and evolution. Results: 14 cases were identified, 78.6% were male, average age 73.4 years (range 26 to 97). 21.4% of cases acquired the infection out of Peru. Risk factors were found in 92.9% of patients (more frequent elderly, hypertension and obesity). The most frequent symptoms were dyspnea, fever and cough, with illness time 8 days (+/- 3); signs of polypnea and respiratory rales. The most frequent laboratory findings were elevated C-reactive protein (average 22 mg / dL) and hypoxemia. The predominant radiological presentation was bilateral interstitial pulmonary infiltration in ground glass. 78.6% (11 of 14 cases) entered mechanical ventilation; 71.4% of the cases received azithromycin, 64.3% hydroxychloroquine and 57.1% broad-spectrum antibiotics; with a 4.7 day hospital stay (+/- 2.4). Conclusion: Those who died from COVID-19 presented bilateral severe pneumonia, more frequent in men, with risk factors (elderly, hypertension and obesity), with a high need for ventilatory assistance.